Hazard identification and risk assessment at a selected petrol station in Klang Valley / Mohamad Saufi Supar - Mohamad Saufi , Supar (2018)
The demand for energy by sector shows that the transportation is the major consumer of energy. With average increment of 5.4% per year, the registration of new vehicle in Malaysia has steadily increased from 2010-2015 (JPJ, 2017). In delivering this primary energy sources to the consumer, petrol station is the primary method in many parts of the world including Malaysia. Due to the nature of handling flammable materials and the incidences which happened at petrol station locally or globally, risk management including fire and explosion at petrol station has started to bring more attention than before. Quantitative Risk Assessment (QRA) which widely being used in chemical processing plant either downstream or upstream is an effective planning tool. It can help to predict the potential major accident occurrences, so the appropriate preventive and mitigating measures can be implemented. In this study, QRA had been conducted on a selected petrol station which was located at Klang Valley with specified objectives. The three main objectives for this study are hazard identification from a checklist, risk evaluation using qualitative and quantitative risk assessment by using ALOHA software and assessment of practices among selected government agencies in giving inputs and approving the petrol station development. Site visit and checklist used has found that the hazards were derived from various categories namely waste and general management, electricity at work, hazardous chemical exposure and fire safety. In general, poor management for these categories could lead to fire and explosion incidents. The results from the QRA study had revealed that the overall individual risk per annum (IRPA) for the petrol station is 7.25 x 10-4 which was not within the risk acceptance criteria (1 x 10-6 frequency per year). Three scenarios has been established to estimate the risk associated to the petrol station such as leakage during offloading of petroleum product from road tanker due to hose or fittings failure, leakage at dispenser area due to failure in safeguarding systems and underground fuel storage tank explosion due to overpressure. The level of concern (LOC) distance for the most significant risk which were flash fire and pool fire, were found beyond the petrol station as shown in the individual risk contour. Survey among the selected government agencies concluded that there is positive process which currently been implemented in evaluating and approving the Development Planning for petrol station projects. However, holistic planning which combines all aspects is deemed necessary so the impact of the associated risk from the operational of petrol station can be identified and minimised during the planning stages.